Functional Inhibition of Natural Killer Cells in a BALB/c Mouse Model of Liver Fibrosis Induced by Schistosoma japonicum Infection - Hu, Yuan; Wang, Xiaoling; Wei, Yuhuan; Liu, Hua; Zhang, Jing; Shen, Yujuan; Cao, Jianping (Frontiers in Cellular and Infection Microbiology, 2020)
Background and Aims Schistosomiasis japonica is a widespread human zoonotic disease, and in China, there are many patients with schistosomiasis suffering from liver fibrosis. Many studies have shown that natural Killer (NK) cells could reduce the progression of hepatic fibrosis by directly killing hepatic stellate cells (HSCs). However, NK cells could not inhibit the progress of liver fibrosis induced by Schistosoma japonicum infection. We aimed to investigate the function of NK cells in schistosomiasis. Methods BALB/c mice were infected with S. japonicum cercariae. The receptors and their proportions expressed on NK cells in the liver and spleen from infected mice were detected using flow cytometry. Levels of IFN-γ, perforin, and granzyme of NK cells, and collagen I, III, and α-SMA of hepatic tissue, were detected using quantitative real-time PCR. Changes in cytokine levels in sera were detected using a cytometric bead array. Liver fibrosis was evaluated using hematoxylin and eosin and Masson staining. NK function in the schistosomiasis model was analyzed. Results From 2 to 4 weeks post-infection, NK cells were activated, with significantly increased levels of effector molecules (IFN-γ, perforin, and granzyme) that peaked at 4 weeks after infection. The proportion of NK cells increased in the liver and spleen from 6 to 10 weeks post-infection. However, the function of NK cells was inhibited from 6 to 10 weeks post-infection with significantly decreased levels of AR, IR, and effector molecules. The levels of IFN-γ, IL-12, and IL-6 in mouse serum peaked at 6 weeks post-infection, and IL-10 and IL-21 levels peaked at 8 weeks post-infection. Hepatic fibrosis markers increased significantly at 6 weeks after infection. Conclusion Our study suggested that NK cells were activated from 2 to 4 weeks post-infection and participated in inflammation in the mouse model. After the S. japonicum laid their eggs, NK cells became inhibited, with decreased levels of both activating and inhibitory NK cell receptors, as well as cytotoxic molecules. In addition, liver fibrosis formed. In mice infected with S. japonicum, the process of liver fibrosis might be alleviated by removing the functional inhibition of NK cells.